Composite particle materials, filler materials, thermal conductive materials

JP2026166796APending Publication Date: 2026-10-14ADMATECHS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025059981
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0014】 上記構成をもつ本発明の複合粒子材料は、表面に樹脂材料が存在するため粒子材料よりも粒径が大きくなって粉塵の形成が抑制できる結果、火炎の伝播が抑制できるため安全性も向上できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166796000001
    Figure 2026166796000001
  • Figure 2026166796000002
    Figure 2026166796000002
Patent Text Reader

Abstract

The problem to be solved is to provide a composite particle material composed of metals but with high safety, as well as a method for manufacturing the same, a filler material, and a thermal conductive material. [Solution] In order to suppress the formation of dust, we conceived the idea of ​​forming composite particles to increase the particle size and completed a composite particle material comprising a particle material dispersed down to primary particles and a resin material having a melting point of 60°C or higher and adhering to the surface of the particle material and / or interposed between the particle materials, wherein the particle material comprises a core made of a metal material having a volume average particle size of 10 μm to 80 μm and a sphericity of 0.9 or higher and containing 50 mass% or more of Al, an insulating film made of alumina with a thickness of 20 nm or more that covers the core without gaps, and a surface treatment layer formed on the surface of the insulating film by reacting a surface treatment agent which is one or more compounds selected from silane compounds and organosilazanes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite particle material, a filler material, and a thermally conductive substance, and particularly to a composite particle material, a filler material, and a thermally conductive substance with excellent thermal conductivity characteristics.

Background Art

[0002] With the progress of miniaturization of semiconductor elements, the generation of a large amount of heat has become a problem. The generated heat is required to be quickly transferred from the semiconductor element to the outside. Therefore, a thermally conductive substance (TIM) with high thermal conductivity is desired.

[0003] As conventional TIMs, resin compositions in which a particle material made of alumina or the like is dispersed in a resin material such as silicone resin have been widely used (for example, see Patent Document 1).

[0004] By the way, it is predicted that the progress of higher density semiconductor packaging will continue in the future, and the accompanying increase in heat generation is unavoidable. As materials with high thermal conductivity, alumina (about 30 W / mK) and boron nitride (about 60 W / mK) are known, but particle materials with even higher thermal conductivity are required.

[0005] Accordingly, as a material with high thermal conductivity, it has been proposed to adopt a metal such as aluminum as the material constituting the particle material (Patent Document 2). Metals such as aluminum often have superior thermal conductivity compared to metal oxides.

Prior Art Documents

Patent Documents

[0006]

Patent Document 1

Patent Document 2

Summary of Invention

Problem to be Solved by the Invention

[0007] Here, it was anticipated that if the metal-based particulate material became airborne, it could ignite due to static electricity, requiring careful handling.

[0008] This invention was completed in view of the above circumstances, and aims to solve the problem of providing composite particle materials, filler materials, and thermal conductive materials that are composed of metals but have high safety. [Means for solving the problem]

[0009] In order to solve the above problems, the inventors conducted diligent research and, as a result, conceived of forming composite particles to increase the particle size in order to suppress the formation of dust, and completed the following invention.

[0010] (1) That is, the composite particle material of the present invention that solves the above problem comprises a particle material dispersed down to the primary particle level, A resin material having a melting point of 60°C or higher, which is attached to the surface of the particle material and / or interposed between the particle materials, It has, The aforementioned particle material is The volume-average particle size is 2 μm or more and 80 μm or less, and the sphericity is 0.9 or higher. A core made of a metallic material containing 50% or more by mass of Al, An insulating film made of alumina, with a thickness of 20 nm or more, that completely covers the core portion without any gaps, It is equipped with.

[0011] By using a resin material as the material to attach to the particle material to form a composite particle material, the use of the composite particle material in the resin composition, which is the main method of using the particle material, will not have any adverse effects.

[0012] (2) Another composite particle material of the present invention that solves the above problems is a particle material dispersed down to primary particles, A resin material having a melting point of 60°C or higher, which is attached to the surface of the particle material and / or interposed between the particle materials, The particulate material described above has a volume average particle diameter of 2 μm or more and 80 μm or less and a sphericity of 0.9 or more, and is composed of a core part made of a metallic material containing 50 mass% or more of at least one selected from Al, Cu and Si, and an insulating coating film made of a metal oxide of the metal constituting the core part and covering the core part without any gaps, .

[0013] The composite particulate material according to the above (1) or (2) may further comprise one or more constituent elements selected from the following (3) to (6). (3) The particulate material comprises a surface treatment layer formed on the surface of the insulating coating film by reacting a surface treatment agent which is one or more compounds selected from silane compounds and organosilazanes. (4) The particulate material has a D10 of 25 μm or more and a D90 of 65 μm or less. (5) The particulate material has a D90 / D10 of 4.5 or less and a D50 / D10 of 2.0 or less. (6) The lower explosion limit concentration is 500 g / m 3 or more, or no lower explosion limit concentration exists. [Advantageous Effects of Invention]

[0014] The composite particulate material of the present invention having the above configuration has a larger particle diameter than the particulate material due to the presence of the resin material on the surface, so that the formation of dust can be suppressed, and as a result, the propagation of flame can be suppressed, whereby safety can also be improved. [Description of Embodiments]

[0015] The composite particulate material, filler material, and thermally conductive substance of the present invention will be described in detail below based on embodiments. Since the composite particulate material of the present embodiment has high thermal conductivity, it can be dispersed in a medium as some kind of filler material (the filler material of the present embodiment) and used as a TIM.

[0016] In particular, a TIM with excellent insulating properties can be provided. The medium may be either liquid or solid, and examples thereof include oils, resin materials, and precursors of resin materials (such as monomers). Examples of the resin material and its precursor include epoxy resins and silicone resins. Further, it can be dispersed in these media as a filler material.

[0017] When used as a filler material, the particulate material of the present embodiment can of course be used alone, and a second particulate material composed of other materials may also be mixed therein. The second particulate material can be composed of an insulator such as ceramics including alumina and silica.

[0018] It should be noted that the numerical values described in the present specification can be used to define a range using the numerical value as the upper limit or lower limit when making amendments, and the range may or may not include the numerical value. In addition, the numerical range "x to y" described in the present specification includes the lower limit x and the upper limit y within the range. A new numerical range can be constructed by arbitrarily combining these upper limit values and lower limit values, as well as the numerical values listed in the specification or Examples. The new numerical range can also be a range that does not include one or both of the upper limit value and the lower limit value. For example, a range greater than x or a range less than y can be adopted. Furthermore, a numerical value arbitrarily selected from any of the above numerical ranges can be used as the upper limit or lower limit value of a new numerical range.

[0019] (Composite particulate material) The composite particulate material of the present embodiment has a particulate material and a resin material. When the resin material adheres to the surface of the particulate material and / or is interposed between the particulate materials, the particle size becomes larger than that of the particulate material contained when the composite particulate material is formed.

[0020] The composite particle material may coat the surface of individual particle materials, or multiple particle materials may be combined into a single composite particle material. In other words, it is also possible to adopt a form in which multiple particle materials are aggregated by a resin material. Furthermore, even if the composite particle material contains multiple particle materials, it can be dispersed into the individual particle materials by melting the resin material.

[0021] The composite particle material preferably has a sphericity of 0.8 or higher to improve fluidity, and lower limits such as 0.85, 0.9, 0.95, and 0.99 can be adopted. Sphericity is determined by taking a picture with a SEM and calculating the (sphericity) = {4π × (area) ÷ (perimeter)} from the area and perimeter of the observed particles. 2 The value is calculated using}. The closer to 1, the closer it is to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is adopted.

[0022] There are no particular limitations on the mixing ratio of particle material and resin material, but the amount of resin material should be such that it can be used for its final application by either further mixing with some resin material to form a resin composition, or by melting it as is without adding any resin material. In other words, the proportion of resin material should be less than the proportion of resin material in the final resin composition. For example, if the particle material makes up 70% by mass in the final resin composition, the amount of resin material contained in the composite particle material should be 30% or less based on the total mass of the composite particle material.

[0023] The composite particle material of this embodiment preferably has a particle size of 500 μm or more and 5000 μm or less. Possible lower limits for particle size are 500 μm, 1000 μm, and 2000 μm, while possible upper limits are 3000 μm, 4000 μm, and 5000 μm. Setting the particle size above the lower limit makes it difficult for dust to form, thus reducing the likelihood of dust explosions. Furthermore, setting the particle size below the upper limit improves the mixability when creating the resin composition.

[0024] ·Particle material The particle material has a core and an insulating coating. The particle material of this embodiment has a volume-average particle size of 2 μm to 80 μm. Preferably, the lower limit of the volume-average particle size is about 2 μm, 5 μm, or 10 μm, and the upper limit is about 65 μm, 70 μm, or 75 μm. These lower and upper limits can be combined arbitrarily. Furthermore, it may be a mixture of two or more types with different particle sizes. The overall packing efficiency is improved by inserting smaller particles into the gaps formed between larger particles.

[0025] Furthermore, when D10 is 15 μm or more and D90 is 95 μm or less, the particle size distribution of each particle constituting the particulate material becomes nearly uniform. In particular, the lower limit of D10 can be set to 20 μm or 25 μm, and the upper limit of D90 can be set to 65 μm, 70 μm, 75 μm, 80 μm or 85 μm. These lower and upper limits can be combined arbitrarily. Moreover, it is preferable that D90 / D10 be 4.5 or less, and more preferable that it be 3.5 or less, 3.0 or less, 2.5 or less, 2.0 or less, or 1.5 or less. And it is preferable that D50 / D10 be 2 or less, and more preferable that it be 1.8 or less, 1.6 or less, 1.5 or less, or 1.2 or less.

[0026] The particle material has a sphericity of 0.9 or higher, preferably 0.95 or higher, and more preferably 0.99 or higher. The core is made of a metallic material containing 50% by mass or more of at least one of Al, Cu, and Si. The metallic material may be a single elemental metal composed of one of Al, Cu, and Si, or an alloy composed of two or more of these elements. In addition, a material can be used that contains other elements besides Al, Cu, and Si, as long as it has metallic properties as a whole.

[0027] The shape of the core is not particularly limited, but it is preferably spherical. A sphericity of 0.9 or higher is particularly preferred, and 0.95 or higher, or even more preferably 0.99 or higher. The particle size of the core is not particularly limited, but it is preferably between 10 μm and 80 μm. Specifically, the lower limit of particle size can be 15 μm, 20 μm, or 25 μm, and the upper limit can be 65 μm, 70 μm, or 75 μm. The lower and upper limits can be combined arbitrarily.

[0028] The insulating film is a film that covers the periphery of the core. The insulating film is composed of a metal oxide. It is preferable that the insulating film completely covers the surface of the core without any gaps. The thickness of the insulating film is either (1) 20 nm or more, or (2) a thickness that maintains insulating properties when a DC 10 V is applied to a single particle. Conditions (1) and (2) may be met simultaneously. The thickness of the insulating film is preferably 30 nm or more, and more preferably 50 nm or more. It is preferable that the insulating film and the core are in close contact. Whether they are in close contact means that when the cross-section of the particle material is observed, the gap between the insulating film and the core is 5 nm or less, and it is especially preferable that they are adjacent without any gaps.

[0029] (1) The thickness of the insulating film is 20 nm or more. The thickness of the insulating film was measured by analyzing the constituent elements using XPS while simultaneously abrading the surface of the particle material at a speed of 10 nm / min with an Ar laser. Specifically, the metal elements in the metal oxide constituting the insulating film and the metal elements constituting the core were quantified, and the depth at which their amounts reversed was defined as the thickness of the insulating film. The abrasion speed of the Ar laser was calibrated using the material forming the insulating film.

[0030] For example, when an insulating film made of alumina is formed on the surface of an aluminum core, the relative amounts of Al were calculated from the peak intensities originating from metallic Al and alumina Al in the XPS measurement. The depth at which the relative amount of metallic Al became greater than that of alumina Al (the depth etched by the Ar laser) was defined as the thickness of the insulating film. For Al, the peak intensities of metallic Al and oxide Al were considered to directly correspond to the relative amounts of Al in each state, and the depth at which the peak intensities reversed was defined as the thickness of the oxide film.

[0031] The metal oxide can be an oxide of the metal element that makes up the core, and in that case, the composition ratio may be the same as or different from the composition ratio of the core. It may also contain elements that are not present in the core.

[0032] (2) The thickness of the insulating film is such that it can maintain its insulating properties when 10V DC is applied to a single particle. The determination of whether insulation properties were maintained was made when the current flowing through the particle material after applying a voltage of 10V directly was measured, and the current, when rounded to one decimal place, was 0mA.

[0033] As an example of a specific measurement device, a pair of tungsten needles with a tip diameter of 1.5 μm, connected to a manipulator, were clamped onto one of the particle materials under a microscope. The current flowing through the material was then observed while gradually increasing the voltage from 0V to 10V using a DC voltage / current generator R6144 (ADC Corporation). As a result, it was determined that insulation was maintained when the current flowing was 0 mA.

[0034] The voltage at which insulating properties can be maintained is relatively higher with increasing insulating film thickness. Furthermore, the voltage at which insulating properties can be maintained varies depending on the insulating film material. Therefore, if the insulating properties of the particle material are insufficient, this can be achieved by increasing the thickness of the insulating film or by changing the insulating film material to one with higher insulating properties.

[0035] The particulate material may have a surface treatment layer formed by reacting it with a surface treatment agent such as a silane coupling agent, a silane compound, or organosilazanes. Examples of silane compounds include compounds having an SiH structure in which organic functional groups such as alkyl groups, phenyl groups, amino groups, phenylamino groups, epoxy groups, acrylic groups, methacrylic groups, vinyl groups, isocyanate groups, and styryl groups are directly connected to Si atoms or connected via spacers, and hexamethyldisilazanes are also examples. The thickness of the surface treatment layer formed on the surface of the particulate material is not particularly limited; for example, if 100% is defined as the amount sufficient to bond with all reactive groups such as OH groups present on the surface of the particulate material, examples of thicknesses of approximately 30%, 50%, 75%, 100%, 150%, and 200% can be given.

[0036] The resin material has a melting point of 60°C or higher, preferably 100°C or higher, and more preferably 120°C or higher. The resin material may be a polymer material such as a thermoplastic resin, or a precursor of a thermosetting resin whose polymerization reaction proceeds upon heating or other means. Specifically, biphenyl-type epoxy resins, O-cresol novolac-type epoxy resins, and phenol novolac-type epoxy resins can be given as examples.

[0037] (Filler material) The filler material of this embodiment includes the particle material of this embodiment. The filler material can be used in TIM, semiconductor encapsulants, underfill materials, etc. The filler material can take the form of particle material as is, a resin composition dispersed in a resin material, or a slurry composition dispersed in a solvent, etc. The filler material may contain other particles of the particle material of this embodiment. For example, alumina or silica particles. The content of other particles can be about 10% to 90% based on the total mass of the filler material. Examples of content can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, etc., and any range can be set as the lower or upper limit of these content.

[0038] (Method for manufacturing composite particle materials) The manufacturing method for the composite particle material of this embodiment is one of the methods for manufacturing the composite particle material of this embodiment described above. This manufacturing method comprises a step of manufacturing a particle material and a step of attaching a resin material to the surface of the particle material.

[0039] The process for manufacturing particulate material involves producing particulate material from a metal material and comprises a particle formation step and an oxide film formation step. The metal material is a material containing metal elements that constitute the core. In particular, it is a material containing 50% by mass or more of at least one of Al, Cu, and Si.

[0040] The particle formation process involves atomizing a molten metal material under an inert atmosphere to produce a raw particle material. The raw particle material obtained by atomizing under an inert atmosphere can be made into highly spherical particles. In this specification, an inert atmosphere is defined as an atmosphere in which the proportion of oxide film formed on the resulting raw particle material is less than or equal to that of air. For example, an atmosphere consisting mainly of inert gases such as nitrogen or argon. The inert atmosphere is maintained only during the process of solidifying the molten material to produce the raw particle material; the process of melting the metal material to create the molten material, and the process after the molten material has solidified into highly spherical raw particle material, do not necessarily require an inert atmosphere.

[0041] The atomization method is not particularly limited, but it is a method of atomizing a molten material by rapidly cooling it. To molten a metal material, one can use any heating method, or one can employ plasma atomization as the atomization method, with the production of the molten material being carried out as part of the atomization process. Examples of rapid cooling methods include contacting the surface of a rotating metal disk, blowing on an inert gas such as nitrogen gas, or blowing on a liquid such as water. Contacting the surface of a rotating metal disk is particularly desirable. The particle size distribution of the raw material particles obtained can be controlled by changing the size, mass, material, and rotation speed of the metal disk. For example, increasing the rotation speed of the metal disk increases the shear force applied to the molten material, which can reduce the particle size of the raw material particles obtained.

[0042] Since the sphericity of the raw particle material obtained in the particle formation process directly affects the sphericity of the manufactured particle material, it is desirable for the raw particle material to have a high degree of sphericity. For example, the sphericity of the raw particle material is preferably 0.9 or higher, and more preferably 0.95 or higher, or 0.99 or higher.

[0043] The oxide film formation process involves heating the raw material particles in an oxidizing atmosphere at a temperature between 600°C and 800°C. The oxidizing atmosphere can be an oxygen-containing gas such as oxygen gas or air, or it can be carried out in the presence of a substance that releases oxygen upon heating. If the temperature is above the lower limit of this range, the surface of the raw material particles can be quickly oxidized and an oxide film can be formed, and if it is below the upper limit of this range, deformation of the raw material particles can be suppressed.

[0044] The heating time is continued until an oxide film with a thickness of 20 nm or more is formed on the surface. For example, when forming alumina as an oxide film from raw material particles composed of aluminum, it was sometimes possible to form an oxide film of the desired thickness by heating in an air atmosphere for about 1 minute to 480 minutes. The appropriate heating time varies in relation to the heating temperature. When the heating temperature is low, a relatively longer heating time is preferable, and when the heating temperature is high, a relatively shorter heating time is preferable. Examples of upper limits for heating time include 300 minutes, 240 minutes, 180 minutes, 120 minutes, 60 minutes, 30 minutes, and 20 minutes, while examples of lower limits for heating time include 3 minutes, 4 minutes, 5 minutes, 10 minutes, 15 minutes, 20 minutes, and 30 minutes. There are no particular limitations on the heating method. For example, heating can be performed using kilns such as roller hearth kilns, pusher kilns, and rotary kilns.

[0045] As an oxide film formation step, the above method of heating can be replaced with a method of forming an oxide film by acid treatment in addition to the above method (acid treatment step). The acid treatment step is a step of immersing raw material particle material in an acidic aqueous solution containing acid with a pH of 1.3 to 2.4 to produce an acid-treated product. The acidic aqueous solution is an aqueous solution containing acid, and contains 50% or more (preferably 70% or more, 90% or more, or 100%) of water based on the mass of the solvent, and may also contain an organic solvent that can be mixed with water. The acid is not particularly limited, and examples include hydrochloric acid, nitric acid, sulfuric acid, acetic acid, oxalic acid, etc. It is preferable to adopt a pH in the range of 1.4 to 1.6. After the acid treatment step, it is preferable to have a washing step in which the acid is washed away with pure water or the like to remove the acid.

[0046] By attaching elements other than those constituting the raw particle material to the surface of the raw particle material before the oxide film formation process, it is possible to form an oxide film containing elements other than those constituting the raw particle material. For example, the raw particle material can be immersed in a solution containing metal elements other than those constituting the raw particle material and then dried, or different types of elements can be incorporated into the surface by sputtering or vapor deposition.

[0047] The surface treatment layer is formed by bringing the surface treatment agent, as described above, into contact with the surface of the particulate material. The surface treatment agent can be brought into contact with the surface of the particulate material either directly or dissolved in a suitable solvent. When brought into contact directly, it can be in liquid or gaseous form. The reaction can be accelerated by heating at an appropriate temperature after or while in contact. Examples of appropriate temperatures include 80°C, 100°C, 150°C, 200°C, and 250°C.

[0048] The method for attaching a resin material to the surface of a particle material is not particularly limited. For example, a composite particle material can be produced by mixing a powdered resin material and a particle material, then performing tumbling granulation at the temperature at which the resin material melts; or by preparing a particle material dispersion solution by dispersing the particle material in a resin material solution prepared by dissolving the resin material in a suitable solvent capable of dissolving the resin material, then atomizing it by spray drying or other means to remove the solvent; or by heating and melting the resin material and the particle material, or by kneading them in the presence of a suitable solvent, and then pulverizing the resulting composition to produce a composite particle material. Furthermore, after atomizing the resin material, a composite particle material can be produced by applying a shear force after mixing it with the particle material in a dry state to attach particles made of the resin material to the surface of the particle material. [Examples]

[0049] The composite particle material of the present invention will be described in detail below based on the following examples.

[0050] <Rating 1> <Preparation of test samples> (Preparation of particle materials) ·Raw material particle preparation process A metallic material consisting of 99.7% Al was heated to 750°C and melted. The molten material was then processed in a disc atomizer under an inert atmosphere (nitrogen atmosphere) to obtain raw material particles. The obtained raw material particles had a sphericity of 0.99, a volume-average particle size of 10.0 μm, and a specific surface area of ​​0.2 m². 2 / g, true specific gravity is 2.7 g / cm³ 3 That was the case.

[0051] • Oxide film formation process The raw material particle was heated in an atmospheric environment at a heating temperature of 650°C, which is below the melting point of Al (660.3°C), for 90 minutes to obtain the particle material used in this example.

[0052] (Preparation of composite particle materials) A composite particle material was prepared by mixing a particle material with an epoxy resin precursor (YX4000H, manufactured by Mitsubishi Chemical Corporation) as the resin material, and granulating it by rolling granulation at a heating temperature of 110°C. This composite particle material was used as the test sample for each test example. Based on the volume of the particle material, the amount of resin material mixed was 10% for Example 1, 15% for Example 2, and 20% for Example 3. A test sample of particle material alone was used as a comparative example.

[0053] The appearance, dust formation properties, and dust explosiveness of the test samples for each example and comparative example were evaluated (Table 1). Dust formation properties were observed after placing the test sample in a glass bottle and shaking it. Dust explosiveness was measured by determining the lower explosive limit concentration.

[0054] [Table 1]

[0055] As is clear from the table, the test samples of each example in which composite particle material was formed together with the resin material were less likely to form dust and also had lower dust explosiveness compared to the test samples of the comparative example, thus improving handling safety.

[0056] <Rating 2> In the raw material particle preparation process in Evaluation 1, the processing conditions of the disc atomizer were changed to obtain particle materials with different particle sizes (particle materials 1-6). Composite particle materials were prepared using these particle materials in the same manner as in Evaluation 1. As a result, by adjusting the amount of resin added, the dust explosiveness was 500 g / m³, similar to Evaluation 1. 3 The composite particle materials described above were obtained. Information regarding the particle sizes of particle materials 1 to 6 is provided below. Note that particle material 4 is the particle material used in evaluation 1.

[0057] [Table 2]

[0058] <Rating 3> After mixing the test samples from each example and comparative example with the resin material, the appearance and physical properties of the cured resin compositions were measured and found to be similar. In other words, it was found that even the aggregated test samples from each example could be mixed into the resin to form a resin composition with excellent dispersibility, just like the test samples from the comparative example, which were dispersed down to primary particles. The ratio of resin material mixed into the test samples was adjusted to ensure that the proportion of particle material in the resin composition was the same, taking into account the amount of resin material contained in the test samples.

Claims

1. Particle material dispersed down to primary particles, A resin material having a melting point of 60°C or higher, which is attached to the surface of the particle material and / or interposed between the particle materials, It has, The aforementioned particle material is The volume-average particle size is 2 μm or more and 80 μm or less, and the sphericity is 0.9 or more. A core made of a metallic material containing 50% by mass or more of Al, An insulating film made of alumina, with a thickness of 20 nm or more, that completely covers the core portion without any gaps, Equipped with, Composite particle material.

2. Particle material dispersed down to primary particles, A resin material having a melting point of 60°C or higher, which is attached to the surface of the particle material and / or interposed between the particle materials, The aforementioned particle material is The volume-average particle size is 10 μm or more and 80 μm or less, and the sphericity is 0.9 or higher. A core made of a metallic material containing 50% by mass or more of at least one of Al, Cu, and Si, An insulating film made of a metal oxide of the metal constituting the core portion, which completely covers the core portion without any gaps, Equipped with, Composite particle material.

3. The composite particle material according to claim 1 or 2, comprising a surface treatment layer formed on the surface of the insulating film by reacting the particle material with a surface treatment agent which is one or more compounds selected from silane compounds and organosilazanes.

4. The composite particle material according to claim 1 or 2, wherein the particle material has a D10 of 25 μm or more and a D90 of 65 μm or less.

5. The composite particle material according to claim 1 or 2, wherein the particle material has a D90 / D10 of 4.5 or less and a D50 / D10 of 2.0 or less.

6. Lower explosive limit concentration is 500 g / m³ 3 The composite particle material according to claim 1 or 2, which is greater than or equal to the lower explosive limit concentration or which does not exist.

7. A filler material containing the composite particle material described in claim 1 or 2.

8. The filler material according to claim 7, A matrix resin material that is compatible with the aforementioned resin material and disperses the aforementioned particle material, A heat-conducting material that possesses thermal conductivity.

9. The thermal conductive material according to claim 8, wherein the filler material further comprises an alumina particle material made of alumina.

Citation Information

Patent Citations

  • Alumina particle material and production method of the same

    JP2017190267A

  • Particulate material and method of producing the same, and filler material

    JP2021098871A